If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -15) = 55 Reorder the terms: 3(-15 + 2x) = 55 (-15 * 3 + 2x * 3) = 55 (-45 + 6x) = 55 Solving -45 + 6x = 55 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 6x = 55 + 45 Combine like terms: -45 + 45 = 0 0 + 6x = 55 + 45 6x = 55 + 45 Combine like terms: 55 + 45 = 100 6x = 100 Divide each side by '6'. x = 16.66666667 Simplifying x = 16.66666667
| 21+x=25+2x | | 35x-3=214 | | 30-18=4(x-1) | | g=0.16(w+40) | | 30+275=1225 | | -4x-8=32 | | 5-.75x=-7 | | 10a-2=7a+1 | | 1x+-8=3(-2x+9) | | 50c-300=250 | | z^2-6X+7=2 | | 3x+24=63 | | 8k^4*2k= | | x^2-12=3 | | 2/3-7/4=5/12 | | -[x-(6x+7)]=7-(9x+3) | | 6-1b=5b+30 | | 5x+2=469 | | 4x-6=-90 | | c=2(4/2) | | 5=1halfm+3 | | -5(z+2)+4z= | | 1.5x+5=2 | | 1+-8=3(-2x+9) | | 4k+2(5k-6)=-3k-39 | | 5.5-x=4.5x | | x+6y=49 | | 6x+12+2x=180 | | 8-4v=-4(6v+8) | | .05x-3.5=.2x-.05 | | y^3-27=0 | | m+12=-14 |